Mycobacterium tuberculosis – atpE gene profile of bedaquiline-treated pulmonary tuberculosis patients at the referral hospital Dr. Soetomo, Indonesia - Muhamad Frendy Setyawan; Ni Made Mertaniasih; S Soedarsono; Zakiyathun Nuha; Yustinus Maladan; Sohkichi Matsumoto (International Journal of Mycobacteriology, 2023)
Background: The atpE gene is a target for bedaquiline (Bdq)-activating drug action and mutations in the gene are fixed to cause resistance. However, changes in the amino acid of ATPase have been little reported from a clinical setting since it was first used in 2015 in Indonesia. This study aims to observe the sequence of nucleotide and amino acid from rifampicin-resistant (RR) pulmonary tuberculosis (TB) patients, both new and relapse cases treated with Bdq. Methods: This is an observational descriptive study performed in the referral hospital Dr Soetomo, Indonesia, at August 2022–November 2022. We performed Sanger sequencing and comparison of the atpE gene from the patient's sputum from August to November 2022 to wild-type Mycobacterium tuberculosis H37Rv and species of mycobacteria using BioEdit version 7.2 and BLAST NCBI software. We also conducted an epidemiological study on patients' characteristics. This study uses a descriptive statistic to show the percentage of data. Results: The total of 12 M. tuberculosis isolates showed that the atpE gene sequence was 100% similar to the wild-type M. tuberculosis H37Rv. No single-nucleotide polymorphisms or mutations were found, and no change in the amino acid structure at position 28 (Asp), 61 (Glu), 63 (Ala), and 66 (Ile). The percentage identity of atpE to M. tuberculosis H37Rv and M. tuberculosis complex was 99%–100%, while the similarity with the other mycobacteria species other than TB (Mycobacterium avium complex, Mycobacterium abscessus, and Mycobacterium lepraemurium) was 88%–91%. Conclusions: This study revealed M. tuberculosis -atpE gene sequence profile of RR-TB patients had no mutations, as the specific gene region, and no change in the amino acid structure. Therefore, Bdq can be continually trusted as an effective anti-tubercular drug in RR-TB patients.